1998
DOI: 10.1023/a:1022304322327
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The results suggest that efforts to increase condom use in general should also influence young men's use of condoms when their partner is using a female method. Providing information to young males about the high prevalence and serious consequences of sexually transmitted diseases may increase dual method use among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Though some research examines heterosexual men’s sexual health [1921], the literature overwhelmingly classifies men’s sexual “risk” as relating to STIs versus pregnancy, and thus rarely includes contraceptive information. Burgeoning research attends to men’s fertility intentions [22], but more in relationship to births than pregnancy prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Though some research examines heterosexual men’s sexual health [1921], the literature overwhelmingly classifies men’s sexual “risk” as relating to STIs versus pregnancy, and thus rarely includes contraceptive information. Burgeoning research attends to men’s fertility intentions [22], but more in relationship to births than pregnancy prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Santelli and colleagues found that about 17% of their community-based sample of teenage and adult women used dual methods [3]. When surveying a nationally representative sample of males, Lindberg and colleagues found that about 17% used a condom when they thought or knew that their female partner was using a hormonal method [4]. In a follow-up study of 104 of 13–25-year-old British women who had received family planning clinic services, and who were initially prescribed the birth control pill, 23 (22%) reported using both hormonal contraception and condoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…4916 Similarly, two cross-sectional studies found lower reported condom use among adolescent oral contraceptive users. 1117 A more recent cross-sectional study, however, did not observe this same pattern. In fact, the investigators found that African American adolescent females who used oral contraception, compared to their counterparts who did not use oral contraception, were significantly less likely to report unprotected vaginal sex and were less likely to screen positive for an STI.…”
Section: Introductionmentioning
confidence: 83%
“…Three previous papers on dual method use and STI risk 111718 categorised respondents as either HC users, a group comprising HC only and dual method users, or non-HC users, a group comprising condom only and contraceptive non-users. When replicating this approach in our data, we found that female non-HC users, relative to HC users, were more likely to be STI-infected (aOR=2.01, 95% CI=1.01–4.00), a finding that aligned with the analysis conducted by Crosby et al 18 In our data, however, the significant association was driven by the high STI prevalence among contraceptive non-users.…”
Section: Discussionmentioning
confidence: 99%